Pasteurized waste milk vs. milk replacer at the same crude protein:metabolizable energy ratio with different energy sources (fat vs. lactose) to pre-weaning Holstein calves: Effects on growth performance, feeding behavior, and health. - Shahryar Kargar; Borhan Moradi; Meysam Kanani; Marzia Albenzio; Mariangela Caroprese; Mohammad Javad Zamiri; Ícaro Rainyer Rodrigues de Castro; Marcos Inácio Marcondes (PLoS ONE)
The improved growth performance of calves at weaning results from an effective pre-weaning feeding strategy. The type and pasteurization process of liquid feed are among the most variable feeding practices affecting calves' growth and health. In previous studies that compared waste milk (WM) vs. milk replacer (MR), little consideration has been given to the variations in chemical composition and feeding behavior between them, and there has been a lack of justification for the crude protein: metabolizable energy (CP:ME) ratio adopted. Hence, this study aimed to evaluate the effects of feeding pasteurized WM or MR differing in energy source (fat vs. lactose, respectively) with similar CP:ME ratio on intake, growth, feeding behavior, and health of newborn Holstein calves. Thirty-two male calves (4-d-old; 40.0 ± 0.58 kg BW) were assigned to the trial and randomly allocated to each liquid feed diet (WM or MR). Calves were housed in individual pens with free access to starter feed and fresh water. Calves were weaned on d 61 and assessed until d 101 as the postweaning period. WM-fed calves had greater total nutrient intake (DM, CP, EE, and ME), weight gain, final BW, skeletal growth parameters, and feed efficiency (d 30). Calves WM-fed sorted less against particles retained on the 2.36-mm sieve but more against particles retained on the sieve of 0.6 mm. In WM-fed calves, the sorting index decreased for feedstuff retaining on the bottom pan compared with MR-fed calves. Irrespective of the type of the liquid feed, all calves sorted for particles retaining on the sieve of 4.75 mm and the bottom pan, and against the particles that were retained on the sieves of 2.36- (MR-fed calves only), 1.18- and 0.6-mm. Starter feed nutrient intake and particle size intake from the sieves of 4.75-, 2.36-, and 1.18-mm increased in WM- vs. MR-fed calves. Eating rate and meal size but not meal frequency and length were greater in WM-fed calves, leading to higher pre- and post-weaning starter feed intake. Calves WM-fed spent less time eating and standing but more time ruminating and lying than MR-fed calves. Calves WM-fed had a lower likelihood of having elevated general appearance (score ≥2; hazard ratio = 2.79), diarrhea (score ≥3; hazard ratio = 1.35), and pneumonia (hazard ratio = 4.77). Calves WM-fed experienced shorter days with elevated general appearance, diarrhea, and pneumonia. Overall, feeding WM led to increased starter feed intake by boosting the eating rate and meal size, promoting greater growth than MR. Additionally, compared with MR, WM feeding increased time spent ruminating and lying and reduced susceptibility to diarrhea and pneumonia.